Shame as a Predictor of the Guilt of Sexual Offenders in the Correctional Institutions - Hamzah, Imaduddin (SCAD Independent, 2021)
Studies of shame and guilt have focused more on normal populations and cultural and religious contexts. The study of this topic for a group of subjects who commit crimes is still limited, especially sexual crimes as actions that are considered socially embarrassing. This study focused on examining the relationship of shame with guilt on inmates of sexual crimes (N = 143) who are carrying out sentences in correctional institutions. Shame and guilt are measured using the Guilt and Shame Proneness (GASP) Scale developed by Cohen et al. This study found a significant positive association so that shame can be a predictor of guilt. This study has implications for the importance of correctional institutions providing treatment to increase shame for prisoners of sexual crimes, thereby preventing the re-offense of their crimes.